Magnetic Resonance Imaging Lesions Associated With Paroxysmal Sympathetic Hyperactivity After Traumatic Brain Injury - Jamie E. Podell; Eric W. Moffet; Uttam K. Bodanapally; Mehrnaz Pajoumand; Luisa M. Silva; Peter Hu; Lujie K. Chen; Nicholas A. Morris; Gunjan Parikh; Gary T. Schwartzbauer; Bizhan Aarabi; Neeraj Badjatia (Neurotrauma Reports)
We performed a clinical-radiographic association study investigating the hypothesis that paroxysmal sympathetic hyperactivity (PSH) occurs in traumatic brain injury (TBI) patients with structural damage to the central autonomic network (CAN). To this end, we identified critically ill acute TBI patients who underwent magnetic resonance imaging (MRI) of the brain between January 2016 and July 2018. All patients were scored retrospectively according to the PSH-Assessment Measure (PSH-AM), which provides a clinical feature score, a diagnosis likelihood score, and a total score. All MRIs were reviewed for lesions within a priori CAN regions of interest, including the brainstem, ventral diencephalon, thalamus, medial temporal lobes, insula, anterior cingulate/medial prefrontal cortex, corpus callosum, and bilateral hemispheric white matter, on diffusion-weighted imaging (DWI), fluid attenuated inversion recovery (FLAIR), and susceptibility-weighted imaging (SWI) sequences. PSH-AM scores were compared using non-parametric tests according to lesion presence in each region and sequence. Imaging features independently associated with PSH-AM scores were ascertained from multivariable linear regression models using backwards elimination feature selection. The strongest predictive models were adjusted for known PSH risk factors including age, sex, and Glasgow Coma Scale (GCS), to determine the independent contribution of imaging features to PSH-AM scores. We found that of 128 patients meeting inclusion criteria, 60 (47%) were clinically diagnosed with PSH. PSH-AM diagnosis likelihood and total scores and clinical diagnosis were strongly associated with CAN lesions. The strongest multivariable model, adjusted for age, sex, and GCS, identified SWI lesions in the corpus callosum and medial temporal lobes as independent imaging predictors of PSH diagnosis likelihood. This exploratory study supports the hypothesis that structural damage to CAN regions is associated with the clinical syndrome of PSH after TBI, and provides foundational evidence for future data-driven studies.